2021
DOI: 10.1371/journal.pmed.1003650
|View full text |Cite
|
Sign up to set email alerts
|

SMS messaging to improve retention and viral suppression in prevention of mother-to-child HIV transmission (PMTCT) programs in Kenya: A 3-arm randomized clinical trial

Abstract: Background Pregnant and postpartum women living with HIV (WLWH) need support for HIV and maternal child health (MCH) care, which could be provided using short message service (SMS). Methods and findings We compared 2-way (interactive) and 1-way SMS messaging to no SMS in a 3-arm randomized trial in 6 MCH clinics in Kenya. Messages were developed using the Health Belief Model and Social Cognitive Theory; HIV messages were integrated into an existing MCH SMS platform. Intervention participants received visit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…The increasing availability and use of mobile technology provide an opportunity for improving health outcomes in low- and middle-income countries [ 9 ], and a variety of mobile health (mHealth) interventions have been developed to support the HIV care cascade [ 10 - 13 ]. Traditionally, mHealth platforms have concentrated on text-messaging or phone call interventions [ 10 , 11 ], and SMS which has been shown to improve HIV retention and VL suppression [ 14 ]. However, current trends are moving toward app-based interventions that allow the tailoring of content to match the needs and preferences of users and can provide multimedia content to enhance participation and further motivate behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability and use of mobile technology provide an opportunity for improving health outcomes in low- and middle-income countries [ 9 ], and a variety of mobile health (mHealth) interventions have been developed to support the HIV care cascade [ 10 - 13 ]. Traditionally, mHealth platforms have concentrated on text-messaging or phone call interventions [ 10 , 11 ], and SMS which has been shown to improve HIV retention and VL suppression [ 14 ]. However, current trends are moving toward app-based interventions that allow the tailoring of content to match the needs and preferences of users and can provide multimedia content to enhance participation and further motivate behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age among trial participants ranged from 17 to 54 years. The primary target group for the text-message interventions were guardians of infant patients [ 19 , 20 , 24 , 25 , 36 , 37 , 39 , 40 , 46 , 47 ] where the mother was the receiver of the text message intervention, whilst the remaining trials solely targeted men [ 22 , 28 ] or women [ 32 , 33 , 35 , 44 , 46 , 48 – 50 ] or both men and women [ 23 , 26 , 27 , 29 31 , 34 , 38 , 41 , 43 , 45 ]. All trials were set in Sub-Saharan Africa with vast majority being set in Kenya (n = 17) followed by South Africa (n = 4) ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical areas in trials were HIV (n = 20), reproductive health (n = 4), antenatal health (n = 4), non-communicable diseases (n = 2), and malaria (n = 1). Ten trials reported that the text message content was developed based on health behavioral theories [ 19 , 24 , 28 , 30 , 32 , 34 , 35 , 37 39 ], eight reported that the content had been pre-tested or developed in consultation with experts, clinical staff and/or potential participants [ 21 , 23 , 25 , 26 , 31 , 39 , 44 , 46 ] and thirteen trials did not report either [ 20 , 22 , 27 , 29 , 33 , 36 , 41 , 43 , 45 , 47 – 50 ]. The content of the two-way text messages varied from supportive, educational, and motivational messages to reminders and quizzes with a two-way component of either replying to the message via text message or phone call or by requesting phone calls or additional information from the sender ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations